A Fast Fault Detection Scheme for Power Converters In Distributed Generation Systems - Gustavo M. S. Azevedo; Marcelo C. Cavalcanti; Francisco A. S. Neves; Fabricio Bradaschia (Eletrônica de Potência)
In this paper, a fault detection algorithm based on voltage disturbances is proposed and analyzed. This method observes the voltage characteristics instead of the current amplitude, that is the most common approach in power distribution electrical systems. The proposed system uses a dual quadrature signal generator for each voltage component in a stationary reference frame to extract its positive- and negative-sequence components. Furthermore, a frequency-locked loop is used to estimate the voltage frequency. The voltage amplitude and frequency instantaneous values are compared with the nominal counterparts by means of hysteresis comparators. As a result, a fast and reliable fault detector system is obtained. Simulations and experimental results are presented to illustrate the feasibility and performance of the proposed scheme.